Evaluation and Management of Aortic Stenosis in Chronic Kidney Disease: A Scientific Statement From the American Heart Association. Issue 25 (22nd June 2021) - Shroff, Gautam R.; Bangalore, Sripal; Bhave, Nicole M.; Chang, Tara I.; Garcia, Santiago; Mathew, Roy O.; Rangaswami, Janani; Ternacle, Julien; Thourani, Vinod H.; Pibarot, Philippe
Abstract : Aortic stenosis with concomitant chronic kidney disease (CKD) represents a clinical challenge. Aortic stenosis is more prevalent and progresses more rapidly and unpredictably in CKD, and the presence of CKD is associated with worse short-term and long-term outcomes after aortic valve replacement. Because patients with advanced CKD and end-stage kidney disease have been excluded from randomized trials, clinicians need to make complex management decisions in this population that are based on retrospective and observational evidence. This statement summarizes the epidemiological and pathophysiological characteristics of aortic stenosis in the context of CKD, evaluates the nuances and prognostic information provided by noninvasive cardiovascular imaging with echocardiography and advanced imaging techniques, and outlines the special risks in this population. Furthermore, this statement provides a critical review of the existing literature pertaining to clinical outcomes of surgical versus transcatheter aortic valve replacement in this high-risk population to help guide clinical decision making in the choice of aortic valve replacement and specific prosthesis. Finally, this statement provides an approach to the perioperative management of these patients, with special attention to a multidisciplinary heart-kidney collaborative team-based approach. Abstract : Supplemental Digital Content is available in the text.